Evaluation of New Power System Based on Entropy Weight-TOPSIS Method. (3rd November 2022) - Liu, Yang; Wang, Yunling; Li, Ting; Ma, Ruiguang; Xu, Ke; Xu, Weiting
Abstract : Under the background of achieving the carbon peaking and carbon neutrality goals on time in China, this study constructs a new power system evaluation index system with new energy as the main body from four aspects of "source, network, load, and storage." This study attempts to use appropriate subjective and objective weighting methods to reasonably distribute index weights and construct an effective, reasonable, scientific, systematic, and comprehensively covered key new power system characteristic index model. From 2017 to 2020, the relevant data for the four dimensions of "source, network, load, and storage" of the power system of three provinces are selected for empirical analysis. The results show that, in the past five years, the performance of the power supply side and network side of the power system in the three provinces was the best and the performance of the load side and energy storage side was slightly insufficient. Specifically, the system outage duration, the number of intelligent sensing terminals, etc., still need to be further optimized and improved.